Driving internationalization through business model innovation: Evidences from an AgTech company. Issue 2 (8th August 2019) - Cavallo, Angelo; Ghezzi, Antonio; Ruales Guzmán, Bertha Viviana
Abstract : Purpose: This paper aims to investigate how a firm may innovate its business model to internationalize. Design/methodology/approach: Owing to its novelty and to the depth of the investigation required to grasp the mechanisms and logics of business model innovation aiming at internationalization, a single case study has been performed related to a company located in North-Western Colombia. Findings: The study provides detailed empirical evidences over the mutual connection and complementarities among value mechanisms of business models. Moreover, this study suggests that BMI fosters internationalization to scale, which, in turn, will require additional changes to match new customer needs as they emerge. Also, the study shows an extension of the action–space of lean startup approaches, intended as scientific approaches to international entrepreneurship. Originality/value: This study connects business model innovation and internationalization as few studies have done before.